A User-Centered Design Approaches for Developing Web Information System for Stroke Care (WISS) - N.H., Hassan; N.A., A. Bakar; M.H.N., Md. Nasir; N.A., Maarop (International Journal of Human and Technology Interaction (IJHaTI), 2018)
Optimizing resources from internet is important because effective stroke care require caregiver have a fruitful of information at increasing efficiency in acute stroke care. With the result shown that stroke becomes the third leading cause of death in world, there is an urge need for the information provided online is reliable. There is still limited information available online to assist in stroke care as well as the right medium to deliver the information to stroke patient. This paper discusses on User-Centered Design (UCD) approaches for designing the prototype for web information system for Stroke Care. The methodology uses are interviews, focus-group discussion and observation, questionnaires and card-sorting activity. This research covers four groups of users: stroke caregivers, two stroke rehab centers, therapists and doctors who handle the structure proposed using UCD approach.